Video-Based Learning Strengthens Critical Thinking in Elementary Science Classes: Media Video Pembelajaran Meningkatkan Berpikir Kritis Siswa IPA SD - Insani, Dianita Agil Insani; Wati, Tri Linggo (Indonesian Journal of Education Methods Development, 2024)
Background: The integration of media in elementary education remains underutilized, limiting opportunities for students to develop essential cognitive skills. Specific Background: Particularly in science education, conventional teaching methods often fail to foster critical thinking among primary school students. Knowledge Gap: Limited empirical studies have examined the role of video-based instructional media in enhancing critical thinking within the context of Indonesian elementary classrooms. Aims: This study investigates the use of video-based learning media in improving fifth-grade students’ critical thinking skills during science lessons on puberty. Results: Utilizing a quasi-experimental design with pre-test and post-test on two groups (n=60), the study found a statistically significant improvement in the experimental group using video media (t=12.331, p<0.001) compared to the control group. The experimental group demonstrated higher gain scores, attributed to engaging delivery, clear visualization, and flexible access to materials. Novelty: This study contributes novel insights into the effectiveness of video-based learning specifically within the Indonesian elementary science education context. Implications: The findings suggest that implementing video media as a teaching tool offers a pedagogical innovation that can support the development of critical thinking skills in young learners and provide practical strategies for educators seeking to enrich science instruction. Highlights :  Use of video media significantly improves students' critical thinking in science learning. Research applies a quasi-experimental design with valid statistical analysis (t=12.331, p<0.001). Study offers practical implications for integrating engaging media in elementary classrooms. Keywords: Video-Based Learning, Critical Thinking, Elementary Education, Science Instruction, Instructional Media